THE QUALITY IMPROVEMENT OF MATEMATICS LEARNING THROUGH THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL WITH SCIENTIFIC APPROACH TO CLASS VI/A STUDENTS AT SD INPRES KASSI MAKASSAR - Nur Shinta Abdullah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
The collecting data techniques were the teachers learning management ability observation sheet and the students’ activity, learning result test, response questionnaire and documentation. The results of the research showed that: (1) the learning process increased from cycle I to cycle II. It could be seen from the percentage of the average score of the teachers and students’ activities. The percentage of the average score of the teachers’ activity in cycle was 80,4% with good category and in cycle II increased 83,04% with good category. While the percentage of the average score of the students’ activity in cycle I was 78,5 with sufficient category and in cycle II highly increased to 85,2 with good category, (2) the students’ learning result by using cooperative learning model with scientific approach of class VI/A students at SD Inpress Kassi Makassar of academic year 2014/2015, increased  classically from cycle I to cycle II, in cycle I the classical completeness was 65,5% and in cycle II incresed to 88,5% from the students who followed the test, (3) the students’ response toward mathematics learning activity through cooperative learning model with scientific approach of class VI/A students at SD Inpress Kassi Makassar of academic year 2014/2015 from 9 aspect asked to the students, the students gave positive response minimally in each aspect by 78,9% namely in the aspect of whether your self confidence increased in giving idea or opinion in the implementation of cooperative learning model with scientific approach, while the other 8 aspect were above 78,9%. The average of positive response percentage was 89,3%